Controlling Surface Wettability for Automated In Situ Array Synthesis and Direct Bioscreening. Issue 36 (26th July 2021) - Lin, Weilin; Gandhi, Shanil; Oviedo Lara, Alan Rodrigo; Thomas, Alvin K.; Helbig, Ralf; Zhang, Yixin
Abstract: The in situ synthesis of biomolecules on glass surfaces for direct bioscreening can be a powerful tool in the fields of pharmaceutical sciences, biomaterials, and chemical biology. However, it is still challenging to 1) achieve this conventional multistep combinatorial synthesis on glass surfaces with small feature sizes and high yields and 2) develop a surface which is compatible with solid‐phase syntheses, as well as the subsequent bioscreening. This work reports an amphiphilic coating of a glass surface on which small droplets of polar aprotic organic solvents can be deposited with an enhanced contact angle and inhibited motion to permit fully automated multiple rounds of the combinatorial synthesis of small‐molecule compounds and peptides. This amphiphilic coating can be switched into a hydrophilic network for protein‐ and cell‐based screening. Employing this in situ synthesis method, chemical space can be probed via array technology with unprecedented speed for various applications, such as lead discovery/optimization in medicinal chemistry and biomaterial development. Abstract : An amphiphilic coating for glass surfaces is reported, on which small droplets of polar aprotic organic solvents can be deposited with enhanced contact angle (small feature size) and inhibited motion (strong binding), permitting fully automated multiple rounds of combinatorial synthesis of small‐molecule compounds and peptides. The amphiphilic coating can be switched to hydrophilic network for protein‐ and cell‐based screening.